A STUDY ON ENGLISH SPECIFIC PURPOSE FOR ENGLISH DEPARTMENT - Ernita Daulay (VISION, 2021)
English can be due to demand of Indonesian in the field of business, technology, education, and research.  The implementation of ESP has revealed some factors, such as students, teachers, and ESP materials that have significant influences on the quality of teaching and learning ESP. These factors require serious attention from stakeholders and ESP practitioners to improve the quality of ESP instruction. The government language policy might emphasize the curricula of formal schools and teachers training for ESP instruction. The quality of teacher of ESP is high contributing to accommodate the teaching and learning ESP course. Besides that, the materials of ESP should be formulated by practitioners of ESP who had knowledge of ESP instruction and the aim of ESP might concern on the improvements in students' proficiency in English. Thus, the students are being better in academic and professional in the work domain.  English for Specific Purposes (ESP) is one of the predominant approaches to language teaching in tertiary education, as it is directed towards the specific needs of the particular specialty students. The paper deals with the role of needs analysis and materials evaluation adjusting ESP courses to the needs of students in tertiary education. Students’ needs analysis is a reference base for both the development of a new ESP course and alterations of an existing ESP course in the changing environment and demands for English language skills. Teaching materials determine the content of the course and affect teaching methods, students’ motivation, vocabulary and language functions taught. The evaluation of teaching materials allows the teacher to constantly improve the ESP course, to better adjust it to the changing needs of students. The theoretical considerations are supported by a survey of students’ needs and their evaluation of teaching materials. The results of the survey reveal whether the students’ needs are met in the ESP course they have attended. The implication of the survey results is that the most topical students’ needs, such as the development of productive skills, and especially speaking skills, do not change over time. Students’ evaluation of the tailor-made ESP course books is also presented, as well as some suggestions to make the ESP courses more attuned to students ‘needs.